Two-terminal connectivity in UWSN probabilistic graphs: a polynomial time algorithm: poster abstract - Altherwy,YN; Elmallah,ES; McCann,JA (Association for Computing Machinery, 2019)
We investigate the likelihood that two nodes are connected in an Underwater Wireless Sensor Network (UWSN) where nodes are floating freely with the underwater currents and the location of nodes at any given time can only be determined in a probabilistic fashion. This problem is #P-hard, thus, we propose HB-Conn2, an algorithm that returns an exact solution in polynomial time when applied on a set of node-disjoint (s, t)-paths.